2013 Fifth International Workshop on Quality of Multimedia Experience (QoMEX) 2013
DOI: 10.1109/qomex.2013.6603211
|View full text |Cite
|
Sign up to set email alerts
|

Automated QoE evaluation of Dynamic Adaptive Streaming over HTTP

Abstract: Dynamic Adaptive Streaming over HTTP (DASH) is referred to as a multimedia streaming standard to deliver high quality multimedia content over the Internet using conventional HTTP Web servers. As a fundamental feature, it enables automatic switching of quality levels according to network conditions, user requirements, and expectations. Currently, the proposed adaptation schemes for HTTP streaming mostly rely on throughput measurements and/or buffer-related metrics, such as buffer exhaustion and levels. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…The authors in [1] have shown that adaptation strategy related parameters (stalling, representation switches) have considerable influence on resulting QoE and more importantly, that they have to be considered on a larger time scale (up to some minutes) than video encoding related parameters (resolution, frame rate, quantization parameter, bit rate) which only influence in the order of a few seconds. In addition to those larger time scales, also impairments, such as stalling and quality switches, have not received much attention in more traditional quality assessment methodologies for subjective testing [12].…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [1] have shown that adaptation strategy related parameters (stalling, representation switches) have considerable influence on resulting QoE and more importantly, that they have to be considered on a larger time scale (up to some minutes) than video encoding related parameters (resolution, frame rate, quantization parameter, bit rate) which only influence in the order of a few seconds. In addition to those larger time scales, also impairments, such as stalling and quality switches, have not received much attention in more traditional quality assessment methodologies for subjective testing [12].…”
Section: Related Workmentioning
confidence: 99%
“…Video coding affects the quality perception of video streaming as stated in literature [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. A variety of video coding standards have been analysed in this context, such as H.264/ advanced video coding (AVC) or H.265/HEVC.…”
Section: Related Workmentioning
confidence: 99%
“…Higher bitrate enables higher degree of user satisfaction [16,34], but also requires higher resolution and more network resources which can be challenging when bandwidth is limited [15,21]. Furthermore, bitrate is related to the transmission efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations